Value Chain Analysis of Peanut Butter for the Economic Reactivation of Manabí, Ecuador - Casanova Castro, Teresa Yajaira (2025)
The current context highlights an urgent need to optimize markets, particularly the agricultural sector, emphasizing the importance of adding value to products and strengthening their value chains as key drivers for enhancing competitiveness and economic outcomes. This study aimed to analyze the peanut butter value chain to identify key factors contributing to the economic revitalization of Manabí, Ecuador. The methodology employed a mixed-methods approach, with a descriptive field study using surveys as the primary data collection technique. Additionally, statistical tests, such as the Kruskal-Wallis test, were applied to identify significant differences among the factors influencing the value chain. The results revealed that the value chain is predominantly influenced by microenterprises in the Chone canton. Furthermore, a discrepancy was identified between years of experience and production levels. The study concluded that, within the context of Manabí and based on the case analyzed, there are opportunities for improvement focused on production optimization and the adoption of new technologies to strengthen manufacturing processes and their impact on the agricultural market.